PROSES ISLAMISASI DAN PENYEBARANNYA DI NUSANTARA - Okvinanda, Aldi; Ramadhan, Fikri; Islamul Hafiz, Vijra; M Farel (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The arrival, Islamization, and spread of Islam in Indonesia is a frequently discussed topic, particularly among Muslim academics. This is inseparable from the numerous questions that frequently arise, such as when Islam first arrived in Indonesia and who played a role in its spread. Based on this, this study aims to examine theories regarding the arrival of Islam and the process of Islamization in Indonesia using a literature review method. The results indicate that the development of Islam in Indonesia occurred peacefully. Theories regarding the arrival of Islam include the Gujarati theory, the Arabic theory, the Persian theory, and the Chinese theory. Meanwhile, the process of Islamization and its spread occurred through various channels, such as trade, marriage, education, Sufism, politics, and arts and culture.